2020
DOI: 10.1371/journal.pone.0237704
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial biofilms colonizing plastics in estuarine waters, with an emphasis on Vibrio spp. and their antibacterial resistance

Abstract: Since plastics degrade very slowly, they remain in the environment on much longer timescales than most natural organic substrates and provide a novel habitat for colonization by bacterial communities. The spectrum of relationships between plastics and bacteria, however, is little understood. The first objective of this study was to examine plastics as substrates for communities of Bacteria in estuarine surface waters. We used next-generation sequencing of the 16S rRNA gene to characterize communities from plas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
38
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(41 citation statements)
references
References 47 publications
3
38
0
Order By: Relevance
“…However, several studies have shown that Vibrio is also abundant in young biofilms (≤7 days) on other substrates, such as chitin, fibreglass, wood, glass, or feathers [ 8 , 14 , 51 , 58 , 59 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, several studies have shown that Vibrio is also abundant in young biofilms (≤7 days) on other substrates, such as chitin, fibreglass, wood, glass, or feathers [ 8 , 14 , 51 , 58 , 59 ].…”
Section: Resultsmentioning
confidence: 99%
“…Following a report of a polypropylene particle from the North Atlantic colonized with a Vibrio strain in high abundance [ 5 ], several studies addressed this issue. Across the world, potentially pathogenic Vibrio species were isolated from plastic debris [ 6 , 7 , 8 ] or detected by specific PCR [ 9 ]. Overall, Vibrio abundances on plastic debris appeared low [ 10 , 11 ], especially when compared to natural particles [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have found that the bacterial communities that accumulated on the surface of MPs were more correlated with human disease than in the water column Xue et al, 2020). Laverty et al (2020) isolated three human pathogens from MPs, including Vibrio cholerae, Vibrio parahaemolyticus, and Vibrio traumatica, which may pose a risk to aquatic ecosystems and human health. Presence of heavy metals in waters may exacerbate the risk of microbes to human health, as a study has found that heavy metals (Cu 2+ and Zn 2+ ) significantly increased the horizontal transfer of plasmids in pathogenic bacteria, which may lead to the prevalence of drugresistant pathogenic bacteria in the water environment (Wang et al, 2021c).…”
Section: Role Of Microorganisms On the Toxic Effects Of Mps And Heavy Metalsmentioning
confidence: 99%
“…Our knowledge of the functional potential as well as the functional capacity of the plastisphere is currently very limited, although the abilities of plastisphere isolates have been more comprehensively tested. There are just three metagenomic datasets available 12,14,15 as well as several studies that measure one or several aspects of plastisphere function (discussed further below), e.g., alkane degradation 93,94,111 , antimicrobial resistance 26,33,49,56,130,218 or pathogenesis 80,114,138…”
Section: The Plastisphere As a Microbial Biofilm On Plasticsmentioning
confidence: 99%
“…Table S4: Potential pathogens (prokaryotic and eukaryotic) found on plastics by the studies reviewed here. Includes references 7,13,26,33,49,56,57,60,69,71,80,83,97,114,127,130,131,137,138,150,362 .…”
Section: Supplemental Materialsmentioning
confidence: 99%